Peer-support groups for cross-border victims of terrorism: Lessons learnt in the UK after the 9/11 and Paris attacks - Watkins Jelena (Temida)
When people become victims of terrorism in a country other than their own, they often face diverse legal, financial, cultural and political difficulties. This paper addresses peer support groups in their various forms (e.g. therapeutic support groups, victim association gatherings, online forums, etc.), as an effective way of helping people affected by cross-border terrorist attacks to deal with the complex problems they face, thus alleviating some of their suffering. It focuses on two major international incidents affecting British nationals: the attacks of 11 September 2001 and the Paris attacks of 13 November 2015. The author was an initiator of peer-support systems for the UK-based bereaved and survivors following both atrocities. Here, she draws on her experience to highlight the benefits and identify potential challenges of such peer-support groups in tackling some of the complex problems individuals affected by cross-border terrorist attacks encounter.